2009
DOI: 10.1053/j.ajkd.2009.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic Syndrome in Diabetic Kidney Disease: An Evaluation and Update of the Definition

Abstract: Background Nephrotic syndrome is defined as urine total protein >3.5 g/d or total protein-creatinine ratio of >3.5 g/g, low serum albumin, high serum cholesterol, and peripheral edema. These threshold levels have not been rigorously evaluated in diabetic kidney disease or using urine albumin, the preferred measure of proteinuria in diabetes. Study Design Diagnostic test study Setting and Participants Adults with type 2 diabetes, hypertension and urine total protein >0.9 g/d enrolled in the Irbesartan in Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
0
22
1
2
Order By: Relevance
“…In 1 study, the corresponding urine albumin level was greater than 2.2 g/d. 100 Urinary loss of large amounts of protein represents a major disruption of the size and charge-selective filtration barrier of a normal glomerulus and is central to the pathophysiological process of other signs and symptoms of nephrotic syndrome. 98,101,102 Patient-reported outcomes, such as discomfort from edema or fatigue or side effects of drugs used to treat the underlying disease or symptoms, are common, but generally not well quantified.…”
Section: Biological Plausibilitymentioning
confidence: 99%
“…In 1 study, the corresponding urine albumin level was greater than 2.2 g/d. 100 Urinary loss of large amounts of protein represents a major disruption of the size and charge-selective filtration barrier of a normal glomerulus and is central to the pathophysiological process of other signs and symptoms of nephrotic syndrome. 98,101,102 Patient-reported outcomes, such as discomfort from edema or fatigue or side effects of drugs used to treat the underlying disease or symptoms, are common, but generally not well quantified.…”
Section: Biological Plausibilitymentioning
confidence: 99%
“…Stoycheff et al 10 showed that in DN patients a baseline 24hUP value of at least 3.2 g ⁄ day was strongly associated with kidney disease progression and the ROC curve confirmed that this variable could discriminate progression from non-progression. In the present study, patients with DN had a mean 24hUP of 8.95 ± 5.98 g ⁄ day.…”
Section: Discussionmentioning
confidence: 94%
“… e For records with spot urine protein‐to‐creatinine ratio without an available albumin to creatinine ratio at the same time, urinary protein excretion was transformed to albumin excretion …”
Section: Resultsmentioning
confidence: 99%